Atomistic modeling of BN nanofillers for mechanical and thermal properties: a review. Issue 1 (26th November 2015) - Kumar, Rajesh; Parashar, Avinash
Abstract : Due to their exceptional mechanical properties, thermal conductivity and a wide band gap (5–6 eV), boron nitride nanotubes and nanosheets have promising applications in the field of engineering and biomedical science. Abstract : Due to their exceptional mechanical properties, thermal conductivity and a wide band gap (5–6 eV), boron nitride nanotubes and nanosheets have promising applications in the field of engineering and biomedical science. Accurate modeling of failure or fracture in a nanomaterial inherently involves coupling of atomic domains of cracks and voids as well as a deformation mechanism originating from grain boundaries. This review highlights the recent progress made in the atomistic modeling of boron nitride nanofillers. Continuous improvements in computational power have made it possible to study the structural properties of these nanofillers at the atomistic scale.